(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In this article, we are talking about the fact that the very concept of “continuity” is explicated in close connection with the categories of “negation”, “removal”, “connection of states”, therefore, it receives the most complete expression in the dialectical law of negation of negation. The most important side (appearance) of this law is continuity, in particular, the continuity of national traditions, which is cultural, historical, ethno-cultural in the context of the dialectic of societies. The phenomenon or principle of continuity is very important for understanding the essence of dialectics as a theory of development and universal connection, firstly, as a moment of negation and, secondly, as a side of the negation of negation.